Expression of cyclin-dependent kinase 2-associated protein 1 confers an independent prognosticator in nasopharyngeal carcinoma: a cohort study. Issue 9 (12th July 2012) - Wu, Li-Ching; Chen, Yi-Ling; Wu, Wen-Ren; Li, Chien-Feng; Huang, Hsuan-Ying; Lee, Sung-Wei; Chang, Shih-Lun; Lin, Ching-Yih; Chen, Yi-Hsien; Hsu, Han-Ping; Lu, Pei-Jung; Shiue, Yow-Ling
Abstract : Background and aim: Low expression of cyclin-dependent kinase 2-associated protein (CDK2AP1) is associated with tumour progression in oral and oesophageal carcinomas, but is not well studied in patients with head and neck cancer and nasopharyngeal carcinoma (NPC). Methods: A rabbit anti-human CDK2AP1 polyclonal antibody was prepared. Immunoblotting of CDK2AP1 was examined in three cell lines and immunoexpression was retrospectively assessed in biopsies of 124 consecutive NPC patients without initial distant metastasis and treated with consistent guidelines. Results: Higher CDK2AP1 expression level was identified in dysplastic oral keratinocytes, compared with two NPC-derived HONE-1 and TW01 cell lines. Low expression of CDK2AP1 (50.8%) was correlated with advanced nodal status (p=0.002) and American Joint Committee on Cancer (AJCC) stage (p=0.004). In multivariate analyses, low CDK2AP1 expression emerged as an independent prognosticator for worse disease-specific survival (DSS; p=0.037) and local recurrence-free survival (LRFS; p=0.042), along with AJCC stage III–IV (p=0.034, DSS; p=0.029, LRFS). Conclusions: Low CDK2AP1 expression is common and associated with adverse prognosticators, conferring tumour aggressiveness through cycle cycle, cell growth or apoptosis cellular processes.